2006
DOI: 10.1176/ajp.2006.163.11.1934
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Trial of a Smoking Cessation Intervention Among People With a Psychotic Disorder

Abstract: These findings demonstrate the utility of a nicotine replacement therapy plus motivational interviewing/cognitive behavior therapy smoking cessation intervention among individuals with a psychotic disorder. Further development of more efficacious interventions is required for those who do not respond to existing interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
124
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 183 publications
(131 citation statements)
references
References 34 publications
5
124
0
1
Order By: Relevance
“…First, the 67% programme completion rate in our study is similar to rates found in other studies in this population (Baker et al, 2006;Khara & Okoli, 2011). The 12-weeks of structured programme in the Butt-Out programme followed by another (optional) 12-weeks of support group was in recognition of the particular needs of individuals who have severe and persistent MI (i.e., cognitive-impairments) that necessitate more time to cover psychoeducational components (Addington, 1998;McChargue et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…First, the 67% programme completion rate in our study is similar to rates found in other studies in this population (Baker et al, 2006;Khara & Okoli, 2011). The 12-weeks of structured programme in the Butt-Out programme followed by another (optional) 12-weeks of support group was in recognition of the particular needs of individuals who have severe and persistent MI (i.e., cognitive-impairments) that necessitate more time to cover psychoeducational components (Addington, 1998;McChargue et al, 2002).…”
Section: Discussionsupporting
confidence: 85%
“…In addition, it is a motivational aid to encourage smokers to measure their progress in terms of smoking cessation. The spectrum grading of this instrument includes non-smokers (0-6), borderline smokers (7-9), low-addicted smokers (10)(11)(12)(13)(14)(15), moderately addicted smokers (16)(17)(18)(19)(20)(21)(22)(23)(24)(25), heavily addicted smokers (26)(27)(28)(29)(30)(31)(32)(33)(34)(35), and very heavy addicted smokers (+36) [37]. It should be noted that each prisoner receiving a score of more than 10 was considered as a smoker in this study.…”
Section: Fagerström's Test For Nicotine Dependence (Ftnd)mentioning
confidence: 99%
“…Many studies have shown the effectiveness of Nicotine Replacement Therapy [19,20,21,22,23] and Motivational Interviewing [24,25,26,27] in terms of smoking cessation. Other studies have shown the effectiveness of the Smoking Cessation Programme for people living with HIV [28,29,30].…”
Section: Introductionmentioning
confidence: 99%
“…47 Several of these programs for improving services, and studies for ascertaining service needs, have been funded by government at either federal or state level. 39,48 Randomised controlled trials have been conducted for smoking 49 and diet, 50 and several lifestyle programs have been evaluated using other methods. 51,52 These developments have followed emerging consensus on policy and care management approaches to mental and physical illness cooccurrence where the mental health system is viewed to be important (not primary care alone), 53 the side-effects of psychotropic drugs are acknowledged 54,55 and the physical health risks encountered more by people with mental illness are better understood.…”
Section: Overviewmentioning
confidence: 99%